P‐223L: Late‐News Poster: New Head‐Up Display System with Ultrahigh Transmittance Using LCs with Negative Dielectric Anisotropy and RGBW Design. Issue 1 (May 2017) - Fang, Liting; Chen, Jianqun; Chen, Yucheng; Huang, Min; Chen, Zhonghuai; Liu, Yuanming; Huang, Qiangcan; Liu, Xiaoli; Zheng, Lihua; Li, Qian; Ling, Ankai; Wu, Ling; et al.
Abstract : We have developed a novel head‐up display (HUD) system with 13.7% transmittance by combining RGBW design, LCs with negative dielectric anisotropy and local dimming backlight. With high transmittance, high contrast ratio and low power, the newly designed HUD system could be more suitable for automotive vehicles.